2004
DOI: 10.1080/0003684042000236048
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of sectoral and aggregate sources of price changes

Abstract: This paper estimates a dynamic common factor model to assess relative importance of the aggregate and the sector-specific factors that determine changes in the prices of individual products. It also examines how aggregate price changes are affected by these factors. Two different specifications of the model are estimated: the baseline model with one aggregate factor, and a second specification with two aggregate factors. In the one factor model, the aggregate factor contributes little to the movements of chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The inclusion of standard macro variables such as output, money supply, interest rate, and exchange rate is primarily motivated by a desire to control for the effects of these variables on individual markets through well known channels. As we mentioned above, aggregate factors such as output, money supply and interest rates have been shown on previous studies to have an important impact on relative prices (Lastrapes, 2006; Nath, 2004). Moreover, the exchange rate with its possible impact on the prices of tradable and nontradable goods also has important implications for relative prices (Betts and Kehoe, 2008).…”
Section: Methodology and Datamentioning
confidence: 76%
See 1 more Smart Citation
“…The inclusion of standard macro variables such as output, money supply, interest rate, and exchange rate is primarily motivated by a desire to control for the effects of these variables on individual markets through well known channels. As we mentioned above, aggregate factors such as output, money supply and interest rates have been shown on previous studies to have an important impact on relative prices (Lastrapes, 2006; Nath, 2004). Moreover, the exchange rate with its possible impact on the prices of tradable and nontradable goods also has important implications for relative prices (Betts and Kehoe, 2008).…”
Section: Methodology and Datamentioning
confidence: 76%
“…For example, Golob and Bishop (1997) reported that there are important differences in the behavior of prices of durables, non‐durables and services. Nath (2004) further suggested that intermediate and investment goods may respond differently than do consumption goods to changes in aggregate factors. These studies, however, do not provide a good explanation as to why these differences exist.…”
Section: Relevant Literature and Theoretical Backgroundmentioning
confidence: 99%
“…The same observation also applies to the sources of price variability. Debelle and Lamont (1997) and Nath (2004) showed that the common factor accounts for only a small part of the variability of different sector prices change, and they gave weight to the idiosyncratic sectoral shocks.…”
Section: Introductionmentioning
confidence: 99%
“…In a broad sense, the difficulty in empirically studying employment fluctuations lies in how to distinguish the influence of an idiosyncratic sector shock propagating through the feedback effects from the influence of an aggregate shock that affects all sectors. Other researchers studying business cycles, such as Sargent and Sims (1980), Forni and Reichlin (1998), Bai (2004) and Nath (2004) have adopted a dynamic index (or factor) model to identify idiosyncratic and common shocks in business cycles, but the methods they have used make no attempt to allow idiosyncratic shocks to propagate across variables. To control the propagation of a shock among economic variables, the structural vector autoregression (VAR) model with residuals that filter out the feedback effects has been widely employed in modern research.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous papers have applied factor models to disaggregated data in a macroeconomic context. Explicit dynamic common factor models have been employed to explain cyclical behavior of sectoral output (Quah and Sargent (1994) and Forni and Reichlin (1998)), world and regional growth rates (Kose, Otrok, and Whiteman (2003)), and disaggregated prices (Bryan and Cecchetti (1993) and Nath (2004)). 5 Stock and 5 There is also an empirical literature that examines the relative price implications of monetary shocks.…”
Section: Introductionmentioning
confidence: 99%